Intrarater and interrater reliability of pulse examination in traditional Indian Ayurvedic medicine - Vrinda Kurande; Rasmus Waagepetersen; Egon Toft; Ramjee Prasad (Integrative Medicine Research)
Background: In Ayurveda, pulse examination (nadipariksha) is an important tool to assess the status of three doshas: vata, pitta, and kapha. Long historical use has been seen as a documentation of its efficacy; however, there is a lack of a quantitative measure of the reliability of the pulse examination method. The objective of this study was to test the intrarater and interrater reliability of pulse examination in Ayurveda. Methods: Fifteen registered Ayurvedic doctors with 3–15 years of experience examined the pulse of 20 healthy volunteers twice, for a total of 600 examinations. The examinations were performed blind and in a random order. Only the current status of dosha-specific methods of pulse examination were considered. Cohen's weighted κ statistic was used as a measure of intrarater and interrater reliability, and a hypothesis of homogeneous diagnosis (random rating) was tested. Following this, we tested whether proportions of ratings were equal between doctors. Results: According to the Landis and Koch scale, the level of reliability ranged from poor to moderate. It was observed that the doctors more frequently diagnosed a combination of two doshas than a single dosha. The κ values were generally larger for experienced doctors (p = 0.04). Conclusion: Experience and proper training have important roles in pulse examination.